2021
DOI: 10.2147/bctt.s256393
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Breast-Q: A Tool to Evaluate Post-Mastectomy Breast Reconstruction

Abstract: Purpose The aim of this systematic review is to update and synthesize new evidence on BREAST-Q questionnaire’s ability to reflect patient-reported outcomes in women who have undergone breast reconstruction surgery (BRS) following mastectomy. Methods PubMed, Science Direct, Google Scholar, Cochrane CENTRAL, and Clincaltrial.gov were searched for relevant studies from January 2009 to September 2021. Any interventional or observational studies that used BREAST-Q to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 92 publications
(110 reference statements)
1
17
0
Order By: Relevance
“…In this way, our findings are consistent with studies indicating that patients undergoing IR increase their quality of life levels compared to those who have not been reconstructed, regardless of the reason and type of surgery (Beugels et al, 2018;Fanakidou et al, 2018;Howes et al, 2016;van Bommel et al, 2020). Besides, these results are consistent with studies concluding that quality of life scores are similar in groups of women with one-stage and two-stage breast reconstruction (Meshulam-Derazon et al, 2018;Seth et al, 2021); one-stage and two-stage breast reconstruction using tissue expanders (Qureshi et al, 2017); one-stage reconstruction with acellular dermal matrices versus conventional two-stage expander or implant use (Negenborn et al, 2018;Srinivasa et al, 2017); and IR with prosthesis and acellular dermal matrix versus two-stage submuscular approach (Caputo et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this way, our findings are consistent with studies indicating that patients undergoing IR increase their quality of life levels compared to those who have not been reconstructed, regardless of the reason and type of surgery (Beugels et al, 2018;Fanakidou et al, 2018;Howes et al, 2016;van Bommel et al, 2020). Besides, these results are consistent with studies concluding that quality of life scores are similar in groups of women with one-stage and two-stage breast reconstruction (Meshulam-Derazon et al, 2018;Seth et al, 2021); one-stage and two-stage breast reconstruction using tissue expanders (Qureshi et al, 2017); one-stage reconstruction with acellular dermal matrices versus conventional two-stage expander or implant use (Negenborn et al, 2018;Srinivasa et al, 2017); and IR with prosthesis and acellular dermal matrix versus two-stage submuscular approach (Caputo et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the type of technique used in breast reconstruction, Meshulam‐Derazon et al ( 2018 ) and Seth et al ( 2021 ) concluded that there are no significant differences in levels of quality of life between women who underwent one‐stage and two‐stage breast reconstruction, except for satisfaction with information. However, Meshulam‐Derazon et al ( 2018 ) report higher scores in sexual well‐being in women with more background diseases; higher levels of psychosocial well‐being in married women; lower values in breast satisfaction in women treated with radiation and higher values among patients with bilateral reconstruction, with the latter subgroup also showing higher physical well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple modules are applicable to various surgical methods. It is widely used by breast surgeons all over the world to assess patients' health-related quality of life [29,30].…”
Section: Questionnaire Settingmentioning
confidence: 99%
“…In the first version, questionnaires related to augmentation mammoplasty, reduction mammoplasty and reconstruction were created ( 48 ). Currently, the Breast-Q is in its the second edition and is the most popular questionnaire for breast reconstruction ( 49 , 50 ). Regarding the Breast-Q, the main domains related to cancer modules are summarized in Table 2 .…”
Section: Introductionmentioning
confidence: 99%